2017
DOI: 10.18632/oncotarget.22425
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine induces cytotoxicity/apoptosis and IL-8 production of human endothelial cells: Related mechanisms

Abstract: Increased levels of oxidized low-density lipoprotein oxLDL) are shown to elevate the risk of cardiovascular diseases such as atherosclerosis, thrombosis, stroke, and myocardial infarction. This is possibly due to the toxic effects of oxLDLs on vascular cells. Various oxLDLs including lysophosphatidylcholine (LPC) and 7-ketocholesterol injure vascular endothelial cells and stimulate inflammatory reaction. However the toxicity of LPC on endothelial cells is not clear. In this study, human endothelial cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 39 publications
2
31
1
1
Order By: Relevance
“…In HUVEC, LPC causes apoptosis, generation of ROS and caspase‐3 activation, which could be inhibited by antioxidants and superoxide dismutase . In two recent reports, LPC has also been shown to trigger ROS production in HUVEC . However, in this work, LPC did not stimulate ROS formation in bEND.3 cells at all, and LPC‐inflicted cell death could not be rescued by ascorbic acid ( Figure ).…”
Section: Discussioncontrasting
confidence: 63%
“…In HUVEC, LPC causes apoptosis, generation of ROS and caspase‐3 activation, which could be inhibited by antioxidants and superoxide dismutase . In two recent reports, LPC has also been shown to trigger ROS production in HUVEC . However, in this work, LPC did not stimulate ROS formation in bEND.3 cells at all, and LPC‐inflicted cell death could not be rescued by ascorbic acid ( Figure ).…”
Section: Discussioncontrasting
confidence: 63%
“…Chang and colleagues demonstrated that LPC induces cytotoxicity/apoptosis and IL-8 production in human endothelial cells via mechanisms dependent on ROS, ATM/Chk2, ATR/Chk2, and PI3K/Akt signaling (67). Pyroptosis is a form of proinflammatory cell death and (68) can be mediated by inflammasome-dependent caspase-1 activation (69) or caspase-11 (70), which is responsible for the cleavage and/or maturation of gasdermin D (GSDMD) and membrane pore formation (71), IL-1β (72), IL-18 (73), HMGB1 (74), and LDH release (75).…”
Section: Discussionmentioning
confidence: 99%
“…LPC plasmatic concentration must be regulated physiologically because 100-µM doses already turn out toxic for most cell types, from OLs (Plemel et al, 2018) to endothelial cells (Akerele and Cheema, 2015). Endogenous LPC is indeed likely involved in atherosclerosis (Chang et al, 2017) and affects the occurrence of major depressive disorders (Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%